Wetland birds of middle Vistula River during breeding season: the impact of human activities on the distribution, abundance and richness of species - Dariusz Bukaciński; Monika Bukacińska; Arkadiusz Buczyński (Studia Ecologiae et Bioethicae)
The inventory of birds was conducted in the years 2005-2010 on the Vistula River section between Dęblin (km 388 of the river) and Podwierzbie (km 435 of the river). The study area includes a southern section of the European Ecological Natura 2000 Site in Poland PLB140004 "Middle Vistula River Valley” (IBA, PL083). On most areas the Vistula flows here within unregulated or relatively little modified riverbed, having features of a natural, lowland, braided river. Sandy islands and braid bars within a main channel, steep banks and old riparian afforestation create the unique breeding habitats of the Vistula River Valley. Especially the river channel habitats provide suitable breeding sites for many rare bird species, constituting for some of them the key-breeding sites. There are, however, fragments of several kilometres, where people transformed the Vistula River in a more noticeable way (Table 1). These are, among others: an urban section within Dęblin boundaries (km 388 to km 393 of the river), a fragment adjacent to Kozienice Power Plant (km 421 to km 426) and the area, where since 2007 gravel for industry has been mined from the river bottom (km 426 to km 431).